Investigation Of The Chemical Composition Of Peppermint Essential Oil Using Gas-Liquid Chromatography (The Peerian Journal, 2025)
This study investigates the chemical composition of essential oil extracted from Mentha asiatica using gas-liquid chromatography (GLC). The method enabled the qualitative and quantitative identification of volatile compounds present in the plant's essential oil. Samples were collected at various stages of plant vegetation, allowing for the assessment of changes in the concentration of key biologically active constituents. The most prominent compounds identified in the oil were menthol, pulegone, carvone, and other terpenoids, which are known for their anti-inflammatory, antiseptic, and antispasmodic properties. The findings emphasize the pharmacological potential of peppermint essential oil and support the need for further research aimed at its application in medicine, cosmetology, and the food industry